2020
DOI: 10.37385/ijedr.v1i1.27
|View full text |Cite
|
Sign up to set email alerts
|

Sell in May and Go Away or Just Another January Effect? Studied of Anomaly in Indonesia Stock Exchange

Abstract: Sell in May and go away is a phenomenon of return anomaly that starts in May and lasts until October. These months are called the worst months of stocks. Conversely, the months of November to April are often referred to as the best months of the stock where a higher rate of return is achieved throughout the year. Although it has not been proven academically, this phenomenon has been mentioned by various media in Indonesia such as Kontan, CNN Indonesia, and Tempo Business which are predicted to correct the JCI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…These researchers' findings support the notion that the COVID-19 pandemic has a detrimental impact on the stock index, so for research question 1 (average monthly return), the theoretical hypothesis is as follows: H1: There is a negative effect of COVID-19 on the average monthly return pattern of LQ45 According to (Wicaksana & Asandimitra, 2018), the stock market on the Indonesian stock exchange does not offer anomalous returns that vary across time periods. (Hayati et al, 2020) note in their study's findings that although the average return increased from November to April due to January's high returns, there was no selling in May, and the increase disappeared on stock exchange in Indonesia. In these circumstances, risk and return have an opposing relationship, showing that the Indonesia Stock Exchange corresponds to the efficient market theory.…”
Section: The Theoretical Frameworkmentioning
confidence: 91%
“…These researchers' findings support the notion that the COVID-19 pandemic has a detrimental impact on the stock index, so for research question 1 (average monthly return), the theoretical hypothesis is as follows: H1: There is a negative effect of COVID-19 on the average monthly return pattern of LQ45 According to (Wicaksana & Asandimitra, 2018), the stock market on the Indonesian stock exchange does not offer anomalous returns that vary across time periods. (Hayati et al, 2020) note in their study's findings that although the average return increased from November to April due to January's high returns, there was no selling in May, and the increase disappeared on stock exchange in Indonesia. In these circumstances, risk and return have an opposing relationship, showing that the Indonesia Stock Exchange corresponds to the efficient market theory.…”
Section: The Theoretical Frameworkmentioning
confidence: 91%
“…Sell in May and Go Away (SIMGA): Schabek and Castro (2017) conclude that even with the control of the weather, behavioral and macroeconomic factors, the sell in May and go away strategy is to have a long position on the market from October 31 till April 30 effect persists in the market. Hayati et al, (2020) showed that there was no significant difference observed between the return of May-October, and November-April and reported about the absence of sell in May and go away effect in the Indonesia Stock Exchange.…”
Section: N the Dividend (D)mentioning
confidence: 95%
“…Hayati et al (2020) meneliti Sell in May and Go Away di Bursa Efek Indonesia menggunakan indeks Harga Saham Gabungan (IHSG), menemukan fakta bahwa meskipun tidak konsisten, rata-rata imbal hasil cenderung lebih tinggi pada periode November-April (best period).…”
unclassified